Metal-layer-assisted coalescence of Au nanoparticles and its effect on diameter control in vapor-liquid-solid growth of oxide nanowires - Guo, Dong Lai (2012)
By using the Au-catalyzed vapor-liquid-solid growth of ZnO and In2O3 nanowires as examples,we demonstrate the critical role of the coalescence of Au catalyst nanoparticles in determining the final diameter distribution of oxide nanowires. The enhanced coalescence is facilitated by a transient liquid-state metal layer in the initial nucleation stage. The onset and the thickness of this layer are dictated by the metal-vapor pressure and the distance between Au catalyst nanoparticles. Equipped with this insight, we are able to control the diameter of the oxide nanowires by tuning the thickness of the liquid-metal layer and the coalescence of the Au nanoparticles.